1988
DOI: 10.1172/jci113570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-hydroxybutyrate on whole-body leucine kinetics and fractional mixed skeletal muscle protein synthesis in humans.

Abstract: Because intravenous infusion of 0-hydroxybutyrate has been reported to decrease urinary nitrogen excretion, we investigated in vivo metabolism of leucine, an essential amino acid, using L-11-'3Cjleucine as a tracer during t9-OHB infusion.Leucine flux during ,B-OHB infusion did not differ from leucine flux during normal saline infusion in nine normal subjects, whereas leucine oxidation decreased 1841% (mean = 30%) from 18.1±1.1 pmol * kg-' * h-1 (P < 0.01), and incorporation of leucine into skeletal muscle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(105 citation statements)
references
References 46 publications
3
100
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] For example, the published values for quadriceps muscle protein synthesis rate in healthy normal subjects are 0.035-0.063% h −1 (SD = 0.009) by Nair et al, 13 0.033-0.064% h −1 (SD = 0.012) by Gibson et al, 1 and 0.036-0.063% h −1 (SD = 0.011) by Nair et al 8 These ranges and standard deviations compare closely with the values reported in the present study (0.023-0.070% h −1 , SD = 0.014) if subject no. 10 is excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] For example, the published values for quadriceps muscle protein synthesis rate in healthy normal subjects are 0.035-0.063% h −1 (SD = 0.009) by Nair et al, 13 0.033-0.064% h −1 (SD = 0.012) by Gibson et al, 1 and 0.036-0.063% h −1 (SD = 0.011) by Nair et al 8 These ranges and standard deviations compare closely with the values reported in the present study (0.023-0.070% h −1 , SD = 0.014) if subject no. 10 is excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, measurement of the rate of skeletal muscle protein synthesis in vivo [1][2][3][4][5][6][7][8][9][10][11] has been achieved by infusing subjects with a stable isotopically labeled amino acid (e.g. (1-13 C)leucine, valine, phenylalanine) and measuring the rate of incorporation of the labeled amino acid into muscle protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot exclude that factors other than insulin deficiency per se might have been responsible for the results observed. Insulin withdrawal was associated with a significant increase in the plasma concentration ofcortisol, glucagon, FFA, ketone bodies, and essential amino acids which have been reported to affect leucine and protein metabolism (13,15,56,58,(70)(71)(72)(73)(74)(75). However, in absence of other hormonal inter-actions in vitro, insulin deficiency decreased the rate of albumin gene transcription and, conversely, insulin replacement increased it (28).…”
Section: Discussionmentioning
confidence: 99%
“…Since increased free fatty acid concentrations have been shown to decrease leucine release in the whole body in dogs (32), as well as at the forearm level in humans (33), and increased ketone body concentrations, in particular fl-hydroxybutyrate, have been shown to stimulate whole-body and muscle protein synthesis (34), the decrease of free fatty acid and ketone body concentrations during insulin might have offset a possible stimulating effect of the hormone itself on amino acid deposition within the forearm. This hypothesis needs to be tested in further studies.…”
Section: Discussionmentioning
confidence: 99%